Knowing and Learning as Creative Action: A Reexamination of the Epistemological Foundations of Education - Stoller, Aaron; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Stoller challenges the long-held view that knowing is a causal and linear act, arguing instead that the process of knowing is interdependent, transactional, and grounded in creative action.
Keywords: Science; Science, general